An optimistic look at the year 1968 - Karl Schiller (Intereconomics, 1968)
After almost twenty years of unparalleled economic growth, the Federal Republic of Germany has experienced a setback in 1967. The Federal Republic's Government is attempting to overcome this crisis with purposive economic policies. INTERECONOMICS had the opportunity of speaking to the Federal Minister for Economic Affairs, Professor Schiller, about development prospects for the German economy for 1968.
Keywords: 330; The German Economy; Interview